Gastrointestinal and external parasites of Enicognathus ferrugineus and Enicognathus leptorhynchus (Aves, Psittacidae) in Chile - Valdebenito, José Osvaldo (2015)
Parasite species are important components of biodiversity, as they provide valuable information about host health, evolutionary relationships, population structures, trophic interactions, the existence of environmental stresses, and climaticconditions. With the aim of describing the parasites associated with parrots of the genus Enicognathus Gray 1840 from central Chile, thirteen austral parakeets, Enicognathus ferrugineus, and five slender-billed parakeets, E. leptorhynchus,were examined between September 2007 and March 2014. The prevalence of ectoparasites and endoparasites was 88.9% and 22.2%, respectively. On eleven of the E. ferrugineus (84.6%) analyzed, and on all of the E. leptorhynchus analyzed (100%), five feather mite species (Pararalichus hastifolia, Genoprotolichus major, Protonyssus sp., Fainalges sp., and Eurydiscalges sp.) were collected. On ten E. ferrugineus (76.9%) and two E. leptorhynchus (40%), the chewing lice Heteromenopon macrurum, Psittacobrossus patagoni, and Paragoniocotes enicognathidis were collected. The nematode Capillaria plagiaticia was collected from three E. ferrugineus (23.1%), and the nematode Ascaridia hermaphrodita was found in one E. leptorhynchus (20%). The presence of C. plagiaticia, Protonyssus sp., Fainalges sp., and Eurydiscalges sp.from the two Enicognathus spp. are new records for Chile and represent new parasite-host associations.